Structural behavior of cemented bahareque for social housing: A case study in Guayaquil City, Ecuador - Mite-Anastacio, Fernando; Tello-Ayala, Ken; García-Troncoso, Natividad; Silva, Christian E.; Malaga-Chuquitaype, Christian; Arévalo, Kleiner; Villao, David (Frontiers in Built Environment, 2022)
The need for social housing creates challenges for engineering. One of the most economical and ecological structural systems for certain areas is the cemented bahareque, which uses Guadua cane, a type of Bamboo with favorable properties for construction. Despite being an ancient technique for the construction of houses, there is not an extensive bibliography that allows making justified decisions regarding their design in most cases. One of the objectives of this article is to present a prototypical design of a housing case with appropriate characteristics to allow a decent occupant’s life with this construction system. For the selected house, the structural behavior is evaluated under gravitational and seismic loads. The constructive criteria that will provide good performance under seismic events are recommended. The most important criteria to follow for the design of wall systems are regularity, continuity, symmetry, bolted connections, rigid diaphragms for mezzanines and continuous maintenance of the Guadua cane elements that make up the framework of the walls. Finally, it is concluded that following the basic criteria of earthquake-resistant design for this type of housing, adequate structural performance can be obtained.